Cloning, expression, and localization analysis of the sucrose transporter gene JcSUT4 in the biofuel plant Jatropha curcas. Issue 5 (3rd September 2018) - Yang, Ziwei; Liu, Yingbo; Han, Hongjun; Ren, Chenxi; Liu, Siwen; Long, Jianmei; Peng, Changcao
ABSTRACT: Sucrose transporters (SUTs) play an important role in regulating fruit growth and development in planta. The fruit of Jatropha curcas, an important tropical tree used as biofuel material, ripens rapidly after flowering. Here, a SUT gene JcSUT4 from J. curcas was cloned and analyzed. JcSUT4, encoding a protein of 500 amino acid residues, was a Type III SUT homolog by a phylogenetic analysis. A transient expression assay in protoplasts showed that JcSUT4 was mainly localized to the plasma membrane. Complementation of yeast sucrose uptake-deficient mutant strains revealed that JcSUT4 was capable of transporting sucrose. JcSUT4 was highly expressed in mature source leaves, as well as in fruits at 30 days after full bloom (DAFB), which was in accordance with the stages of fruit swelling and ripening. This work shows that JcSUT4 may participate in the fruit growth and development of J. curcas, particularly be involved in sucrose storage in fruit. Taken together, our results provide new insights into the molecular mechanisms underpinning of SUTs in Jatropha .